The Role of the Pancreatic Extracellular Matrix as a Tissue Engineering Support for the Bioartificial Pancreas - Santos da Silva, Thamires (2024)
Type 1 diabetes mellitus (T1DM) is a chronic condition primarily managed with insulin replacement, leading to significant treatment costs. Complications include vasculopathy, cardiovascular diseases, nephropathy, neuropathy, and reticulopathy. Pancreatic islet transplantation is an option but its success does not depend solely on adequate vascularization. The main limitations to clinical islet transplantation are the scarcity of human pancreas, the need for immunosuppression, and the inadequacy of the islet isolation process. Despite extensive research, T1DM remains a major global health issue. In 2015, diabetes affected approximately 415 million people, with projected expenditures of USD 1.7 trillion by 2030. Pancreas transplantation faces challenges due to limited organ availability and complex vascularization. T1DM is caused by the autoimmune destruction of insulin-producing pancreatic cells. Advances in biomaterials, particularly the extracellular matrix (ECM), show promise in tissue reconstruction and transplantation, offering structural and regulatory functions critical for cell migration, differentiation, and adhesion. Tissue engineering aims to create bioartificial pancreases integrating insulin-producing cells and suitable frameworks. This involves decellularization and recellularization techniques to develop biological scaffolds. The challenges include replicating the pancreas’s intricate architecture and maintaining cell viability and functionality. Emerging technologies, such as 3D printing and advanced biomaterials, have shown potential in constructing bioartificial organs. ECM components, including collagens and glycoproteins, play essential roles in cell adhesion, migration, and differentiation. Clinical applications focus on developing functional scaffolds for transplantation, with ongoing research addressing immunological responses and long-term efficacy. Pancreatic bioengineering represents a promising avenue for T1DM treatment, requiring further research to ensure successful implementation.